2019
DOI: 10.1590/0104-9224/si24.15
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Embrittlement and Softening in Heat Affected Zone of High Strength X90 Pipeline Steels

Abstract: The embrittlement and softening behaviors in heat affected zone of X90 pipeline steel were studied, and the influence of weld thermal cycle on microstructure and mechanical properties were discussed by combining the effect of peak temperature on the phase transition point (Ar3). Results show that there are embrittlement and softening zones existed in heat affected zone of X90 pipeline steel. The peak temperature greatly affected the austenitizing and its grain size, thereby affected phase transition during coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This softening reported by the literature is usual in API X80 steel 14,65,[68][69][70][71][72][73][74] , and is due to the predominance of polygonal ferrite 65,72,73 . However, some works 14,68,74 state that the softening of HAZ may be more serious and a study on high-strength pipeline steel should not only pay attention to the embrittlement but also to the softening of the welding heat affected zone 73 , because the reduction in hardness can be around 10-20% in comparison to the base metal 70 . Other works 14,[68][69][70][71] have shown that differences inferior to 10% are not problematic.…”
Section: Mechanical Properties and Microstructural Characterizationmentioning
confidence: 80%
See 1 more Smart Citation
“…This softening reported by the literature is usual in API X80 steel 14,65,[68][69][70][71][72][73][74] , and is due to the predominance of polygonal ferrite 65,72,73 . However, some works 14,68,74 state that the softening of HAZ may be more serious and a study on high-strength pipeline steel should not only pay attention to the embrittlement but also to the softening of the welding heat affected zone 73 , because the reduction in hardness can be around 10-20% in comparison to the base metal 70 . Other works 14,[68][69][70][71] have shown that differences inferior to 10% are not problematic.…”
Section: Mechanical Properties and Microstructural Characterizationmentioning
confidence: 80%
“…The former is not a problem for impact toughness because the presence of polygonal ferrite promotes high Charpy-V results, although it can impair the mechanical strength when the difference in hardness is 20% greater than the base metal 14,65,68,74 . However, the latter can be a significant problem because the toughness is indubitably affected by the presence of a 'necklace' of micro-phases around the prior austenite grain boundaries 65,73,76 . Recently, MA constituents have been under scrutiny because their significance on mechanical properties is ambiguous, particularly in terms of tensile and toughness properties.…”
Section: Concerns About Safe Welding Proceduresmentioning
confidence: 99%
“…The hardness values in the HAZ and the FZ of the welded stainless steel shows that the hardness of the HAZ and FZ are reasonably comparable within same weld region (HAZ or FZ) irrespective of the heat input. The higher the heat input the slower the cooling rate which allows for grain refinement within the HAZ and leads to the formation of coarse grains (Jovicic et al, 2015;Gu et al 2019;Amuda et al 2020) that should engender relatively softer HAZ.…”
Section: F Hardness Testmentioning
confidence: 99%
“…Usually, the softening phenomenon potentially appeared in the coarse-grained zone, intercritical zone or fine-grained zone of HAZ, namely, CGHAZ, ICHAZ and FGHAZ, respectively [11][12][13]. Gu et al [14] suggested that the larger-size polygonal ferrite (PF) and granular ferrite formed from the ununiform prior austenite resulted in softening phenomenon. In order to reduce the HAZ softening, researchers have put forward many methods [15,16].…”
Section: Introductionmentioning
confidence: 99%